Efficiency improvement of ships operation by water-fuel emulsion using - Malahov, Aleksey; Gudilko, Roman; Palagin, Alexander; Maslov, Igor (Eastern-European Journal of Enterprise Technologies, 2016)
The technology of using water-fuel emulsions during operation of vessels serving oil platforms is investigated. When considering the process of burning water fuel emulsions the diffusion theory of combustion with the scheme effective film. The mechanism of combustion of water-fuel droplets is described and the main theoretical expressions were applied. The results of physical experiments relating to the influence of water concentration on the combustion process of the emulsion were obtained during the operation of the main engine of the vessel. It was established how the concentration of water components influence the burning process water fuel emulsions. For different load modes for the main engine of the set numerical values of fuel economy depending on the water concentration in the feed for the combustion of water-fuel emulsion. The result of maximum fuel economy equal to 13.42 % is obtained at the engine load of 80 %. It is shown that with the increasing humidity of the fuel from 1 % to 15 % the temperature of exhaust flue gases of ships is reduced by 52.7 oС. It is established that the presence of water in a lightweight diesel fuel under certain conditions can have a positive effect on the combustion process, which leads to improved characteristics of the resulting torch of fuel burning and heat dissipation.